A novel disturbance observer-based backstepping controller with command filtered compensation for a MIMO system. Issue 16 (November 2016) - Rashad, Ramy; Aboudonia, Ahmed; El-Badawy, Ayman
Abstract: This paper presents a novel disturbance observer-based trajectory tracking controller based on the integral backstepping approach. To avoid the complexity of analytically calculating derivatives of virtual control signals in the standard backstepping technique, a command filtered backstepping approach is utilized. The proposed control approach is formulated for a class of nonlinear MIMO systems and provides robustness against external disturbances. This approach is applied on an aerodynamic laboratory setup known as the twin rotor MIMO system (TRMS). Stability analysis of the proposed controller is presented using Lyapunov stability arguments and singular perturbation theory. Simulation studies show that the proposed controller successfully allows the system outputs to track arbitrary reference trajectories and reject arbitrary constant disturbances that may occur due to partial actuator failure. The reliability and effectiveness of the approach is validated experimentally by implementation of the proposed controller on a hardware-in-the-loop system. Abstract : Highlights: This paper develops a command filtered backstepping controller for a MIMO system. Use of command filtering eliminates the need to differentiate command signals. The controller utilizes a nonlinear disturbance observer for disturbance rejection. Stability proof using singular perturbation technique is provided. Simulation and experimental validation of the proposed controller is carried out.